Wear and friction characteristics of atmospheric plasma sprayed Cr3C2–NiCr coatings. (2nd July 2020) - Chhabra, Pankaj; Kaur, Manpreet
ABSTRACT: The present work focuses on investigating the wear and friction characteristics of the Atmospheric Plasma Sprayed Cr3 C2 -NiCr coatings deposited onto the surface of die steel material. The as-sprayed specimens were characterized. The coating porosity, bond strength and microhardness values were evaluated. Wear tests were performed on the high-temperature pin-on-disc tribometer at room temperatures, 400°C and 800°C under two loads as 25N and 50N in the laboratory. The wear mechanisms of all the worn-out samples were studied by scanning electron microscopy (SEM) technique. The specific wear rates and the coefficient of friction values were analyzed. The developed coating showed better wear resistance than its uncoated counterpart. The coefficient of friction values for coated specimens decreased at elevated temperatures. At room temperatures, the wear mode was observed to be adhesive and further at elevated temperatures of testing, the wear mode was observed to be the combination of oxidative, adhesive and abrasive.